Promotion of a Sports Culture in Kenya - Mulili, Benjamin Mwanzia; Mwangi, Samuel Maina; Kinyuru, Reuben Njuguna (Journal of Business and Strategic Management, 2025)
Purpose: This paper reviewed conceptual literature related to the promotion of a sports culture in Kenya. The paper highlighted the benefits associated with engaging in physical exercises and it emphasized the role of health-promoting sports clubs as suitable avenues for undertaking organized physical activities. Methodology: The paper was based on extensive review of extant conceptual, theoretical, and empirical literature related to promotion mix elements, health-promoting sports clubs, and adoption of a physical activities culture. Findings: The paper found limited use of the promotion mix elements of advertising, personal selling, sales promotions, public relations, and direct marketing in the promotion of a sports culture among academic staff of chartered public universities in Nairobi City County, Kenya. Unique Contribution to Theory, Policy and Practice: The paper points out areas that need to be addressed by policy makers and practitioners in order to improve membership to health-promoting sports clubs, and to encourage more people to adopt a physical activities culture.